Interactions between beech and oak seedlings can modify the effects of hotter droughts and the onset of hydraulic failure - Mas, Eugénie; Cochard, Hervé; Deluigi, Janisse; Didion‐Gency, Margaux; Martin‐StPaul, Nicolas; Morcillo, Luna; Valladares, Fernando; Vilagrosa, Alberto; Grossiord, Charlotte (The New phytologist, 2024)
Summary Mixing species with contrasting resource use strategies could reduce forest vulnerability to extreme events. Yet, how species diversity affects seedling hydraulic responses to heat and drought, including mortality risk, is largely unknown. Using open‐top chambers, we assessed how, over several years, species interactions (monocultures vs mixtures) modulate heat and drought impacts on the hydraulic traits of juvenile European beech and pubescent oak. Using modeling, we estimated species interaction effects on timing to drought‐induced mortality and the underlying mechanisms driving these impacts. We show that mixtures mitigate adverse heat and drought impacts for oak (less negative leaf water potential, higher stomatal conductance, and delayed stomatal closure) but enhance them for beech (lower water potential and stomatal conductance, narrower leaf safety margins, faster tree mortality). Potential underlying mechanisms include oak's larger canopy and higher transpiration, allowing for quicker exhaustion of soil water in mixtures. Our findings highlight that diversity has the potential to alter the effects of extreme events, which would ensure that some species persist even if others remain sensitive. Among the many processes driving diversity effects, differences in canopy size and transpiration associated with the stomatal regulation strategy seem the primary mechanisms driving mortality vulnerability in mixed seedling plantations. See also the Commentary on this article by Wright, 241: 955–957.